(untitled) (Research, Society and Development, 2020)
This article is inserted in the field of History of Education, under a cultural approach, articulating the domain of the History of Intellectuals. We aim to investigate the acting of the intellectual Antônio de Sousa in the educational context of the Rio Grande do Norte during the period of the First Republic (1889-1930). For this purpose, we use the subject’s biographies as sources, made operational by the historiographic method of heuristics and hermeneutics. Minutes from cultural institutions, government messages, magazines and periodicals were also taken as sources. Antônio de Sousa is seen in this work as an intellectual according to the discussions proposed by Sirinelli (1998), understanding him as a member of a creative elite and cultural mediator. The construction of this article also starts from the tripod place of speech, practice and writing, proposed by Michel de Certeau (1982), so that, initially, we present the figure of Antônio de Sousa, then his acting in favor of potiguar education and, finally, we analyzed his writing in newspapers at the time with regard to educational themes, especially female education. Thus, we bring to light a subject in his space-time and networks of sociability, consolidating himself as an intellectual in favor of education, in the still recent republican regime.